Zirkulationsbedingte Verteilungsmuster von Niederschlagsanomalien im tropischen Bereich von Südafrika bis Australien - Jacobeit, Jucundus (ERDKUNDE, 1989)
Tropical rainfall and upper circulations not only show some longterm trends but also interannual variations which allow one to study different patterns of anomalies on the basis of selected years or seasons with significant deviations. Within the tropics from Southern Africa to Australia four summer monsoonal seasons, with different distributions of coherent rainfall anomalies, are identified on the basis of monthly rainfall data of 50 stations within the period 1968-85, using a special rainfall index which compensates for different rainfall levels and considers different orders of variations. The corresponding circulation patterns have been studied by means of factor analysis of 200 hPa- pentad-windfields, deviations of the seasonally averaged 200 hPa zonal wind component and 700 hPa relative vorticity, and of frequency distributions of above average 700 hPa cyclonic wave indices within two tropical latitudinal bands. The upper wind fields extending from the equator up to 48°S allow one to recognize the interactions between tropical easterlies and extratropical westerlies, and demonstrate quite different patterns of variations which partly fit rather simple concepts of strengthened or weakened easterlies, but partly reveal some other features such as varying positions of anticyclonic centres, upper troughs or wave maxima, transequatorial flows with extended northerlies or spreading westerlies, and alternating tendencies of lower level vorticities.